A hideous and intolerable... Anecdote? Moby-Dick and questions of truth seen from the human and the non-human side - Breinig, Helmbrecht (Anecdotal Modernity, 2020)
In Moby-Dick, a novel that is also a search for meaning, truth, and the nature of reality, Herman Melville makes use of multiple textual forms and genres, among them the anecdote. Indeed, since all human hunting stories are anecdotes, the novel as a whole might be seen as an anecdote of gigantic proportions. It contains a number of what zoologists call ethological anecdotes describing the observed behavior of non-human animals. Just as Melville through his narrator Ishmael rejects a purely allegoric or symbolic reading, he also points out the limitations of the anecdotal even in its transdifferent oscillation between fact and fiction. As he exemplifies by the inset "Town-Ho's Story, " the anecdote's focus on external events makes it an epistemological tool only in the restricted sense of providing factual material while leaving its truth value undecided. When we turn to the question of truth seen from the hunted animals' side, we have only very limited insight. However, Melville presents the whales' point of view when he has Ishmael reflect on their gaze and the awareness reflected by it. He thus makes clear that what is needed in our interaction with other animals is empathy and trans-species compassion, the importance of which Jacques Derrida insists upon in his last books.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Epistemological uncertainty; Hermann melville; Moby-Dick; Non-Human animals